Literasi Digital Calon Guru Pendidikan Keagamaan Katolik: Penggunaan Spreadsheet Elektronik untuk Pengolahan Nilai Sederhana - Lisarani, Varetha; Meman, Oktavianey G. P. H.; Mukarramah, Mukarramah (Vocat : Jurnal Pendidikan Katolik, 2025)
This study explores digital literacy among prospective Catholic Religious Education (PKK) teachers concerning their ability to use electronic spreadsheet programs for simple grade processing. Using descriptive statistical analysis with 75 respondents, it was found that the average test score of the students was 55.51, with a high variance (170.388) and a standard deviation of 13.053. The analysis results showed that 16% of the students demonstrated low ability, 65.3% had moderate ability, and 18.7% showed high ability. These findings indicate a gap in technological literacy that needs to be addressed to enhance students' skills in educational data management. The recommended actions include intensive training, the use of peer tutoring methods, the integration of technology into lectures, and access to relevant digital resources. These efforts aim to create a collaborative learning environment and improve students' readiness to carry out administrative and teaching tasks in the future. This study emphasizes the importance of targeted interventions in teaching and technology training to optimize digital literacy among prospective teachers.